1997
DOI: 10.1074/jbc.272.43.26940
|View full text |Cite
|
Sign up to set email alerts
|

Deleted in Colorectal Carcinoma (DCC) Binds Heparin via Its Fifth Fibronectin Type III Domain

Abstract: Allelic deletions on chromosome 18q in Ͼ70% of primary colorectal tumors prompted the search for a tumor suppressor gene at that locus. An early result of this search was the cloning of a putative cell-surface receptor, DCC (deleted in colorectal carcinoma) (1). While the cloning of DCC brought much excitement that a tumor suppressor gene responsible for many colorectal cancers had been identified, 7 years later, the evidence that DCC is the putative tumor suppressor located on chromosome 18q remains inconclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 18 publications
0
59
2
Order By: Relevance
“…sNetrin binds to DCC and UNC5 fragments with 1:1 stoichiometry, and interactions of the receptors with sNetrin appear to be mutually exclusive. We also find that netrin binding is mediated by the same 11-amino acid loop on DCC previously identified as a heparin binding site (11). Since heparin does not compete with netrin for DCC binding and we are unable to detect direct interactions between heparin and DCC, interactions between DCC and heparin observed in earlier studies appear to have been mediated by netrin.…”
Section: From the Howard Hughes Medical Institute And The Department mentioning
confidence: 40%
See 3 more Smart Citations
“…sNetrin binds to DCC and UNC5 fragments with 1:1 stoichiometry, and interactions of the receptors with sNetrin appear to be mutually exclusive. We also find that netrin binding is mediated by the same 11-amino acid loop on DCC previously identified as a heparin binding site (11). Since heparin does not compete with netrin for DCC binding and we are unable to detect direct interactions between heparin and DCC, interactions between DCC and heparin observed in earlier studies appear to have been mediated by netrin.…”
Section: From the Howard Hughes Medical Institute And The Department mentioning
confidence: 40%
“…Heparin-It has been reported that DCC contains a heparin-binding site within its fifth Fn repeat (11). Consequently, our observation that sNetrin binding mapped to this same Fn repeat of DCC (Figs.…”
Section: Binds Netrin Via a Specific Loop In Dcc-fn(5) But Does Nmentioning
confidence: 65%
See 2 more Smart Citations
“…Bennett et al 1997). Recent studies using Drosophila mutants and transgenic mice indicate that, for instance, sulfation of heparan sulfate (HS) has important roles in developmental processes .…”
Section: Introductionmentioning
confidence: 99%